Quark launches QuarkXPress 9. IN Web Designing. - Dove, Jackie
Publishing app transitions into multiplatform publishing system for print and dynamic designs.
Keywords: Quark, Inc; Desktop publishing; Electronic publishing; QuarkXPress (Computer file); Web sites -- Designs; App Studio; e-book reader; QuarkXPress 9.